Immobilization of escherichia coli outer membrane protein on magnetic nanoparticles for application in the separation of water-in-oil emulsions (2019)
Biosurfactants are biomolecules capable of altering interfacial tension of emulsions. Since they are produced by different microorganisms and are biodegradable their use in water-in-oil separation is being studied. In this work, Escherichia coli outer membrane protein, OmpN, was immobilized on magnetic nanoparticles (MNPs) to explore their application as biosurfactant in the separation of water in oil emulsions. MNPs were synthesized via co-precipitation with a hydrodynamic radius of 122 nm in water, which increased to 196 nm upon immobilization of OmpN. SEM images showed a marked tendency of the MNPs to agglomerate after lyophilization processes. This can be addressed by sonication in a dispersion medium prior to their use. FTIR spectra demonstrated immobilization of protein on the surface of silanized MNPs. TGA analysis showed a functionalization efficiency of 8%. The biosurfactant activity of free and immobilized protein was evaluated with the aid of pendant drop shape assays and direct separation of model emulsified media. Pendant drop shape assays showed that OmpN, interfacial tensions for the same media remained above 20 mN/m most likely due to the tendency of the protein to form clusters in both the free and immobilized state. Separation of model emulsions was carried out by adding 30.000 ppm of functionalized nanoparticles to diesel emulsions. Treated water was analyzed by UV-visible spectroscopy using pure water as blank. Nanoparticles were then washed using alkaline water (pH 10) and reused. Emulsion separation capabilities of the nanoparticles did not decrease after 3-4 reuses.